Structural characterisation of the Chaetomium thermophilum Chl1 helicase - Hodáková, Zuzana (PLoS One, 2021)
Chl1 is a member of the XPD family of 5’-3’ DNA helicases, which perform a variety of roles in genome maintenance and transmission. They possess a variety of unique structural features, including the presence of a highly variable, partially-ordered insertion in the helicase domain 1. Chl1 has been shown to be required for chromosome segregation in yeast due to its role in the formation of persistent chromosome cohesion during S-phase. Here we present structural and biochemical data to show that Chl1 has the same overall domain organisation as other members of the XPD family, but with some conformational alterations. We also present data suggesting the insert domain in Chl1 regulates its DNA binding.